Developing community economic empowerment strategies through productive zakat, infaq, and sadaqah funds using the analytic network process - Nur Dalilah; Muhammad Syukri Albani Nasution; Juliana Nasution (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study aims to formulate strategic priorities for optimizing community economic empowerment through the productive utilization of Zakat, Infaq, and Sadaqah (ZIS) funds in North Sumatra, Indonesia. The study employed the Analytic Network Process (ANP) based on pairwise comparison judgments from nine purposively selected experts representing academics, regulators, and practitioners in Islamic social finance and community empowerment. Data were analyzed using Super Decisions through the unweighted, weighted, and limit supermatrix procedures. The consistency ratios ranged from 0.03 to 0.08, indicating acceptable consistency. The results identified insufficient business mentoring (18.6%), low Islamic financial literacy (16.4%), and inadequate household economic capacity (14.7%) as the highest-priority problems. The leading strategic alternatives were developing entrepreneurial capacity (23.1%), strengthening ZIS education and Islamic financial literacy (20.5%), and strengthening partnerships and market access (17.2%). These findings indicate that productive ZIS requires an integrated empowerment approach that combines financial assistance with mentoring, entrepreneurship development, financial literacy, market access, and stakeholder collaboration. The study contributes a priority-based ANP framework for strengthening sustainable and accountable productive ZIS management within the principles of Maqashid al-Shariah.